Category shift and its meaning shift in the translation of ANTARA news’ press releases (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
This research aimed to investigate the types, the most dominant types of category shifts, and meaning shifts that occurred in the category shift found in the English to the Indonesian press releases on ANTARA news. The descriptive qualitative was used to investigate the data. The theories were applied, namely Catford (1965) and Simatupang (2000). Furthermore, this research took three samples of the press releases on ANTARA news. The data were taken from looking at the official website of ANTARA news. Then, the data were put in the table consisting of SL and TL. After resolving the analysis of each category shift, the researcher found 306 data. Structure shifts occurred to the number of 139 data or 45 %, intra-system shifts were 85 data or 28 %, unit shifts were 72 data or 24 %, and class shifts occurred are 10 data or 3 %. The most dominant category shift was structure shift. Furthermore, the result of meaning shifts, there were 300 data or 98% for no meaning shift. The result of the specific to generic and vice versa as well as the cultural point of view had 3 data or 1% for each type.